INHIBITION BY ANTIBIOTICS OF THE GROWTH OF BACTERIAL AND YEAST PROTOPLASTS - Shockman, Gerald D. (1962)
Shockman, Gerald D. (Temple University School of Medicine, Philadelphia, Pa.) and J. Oliver Lampen. Inhibition by antibiotics of the growth of bacterial and yeast protoplasts. J. Bacteriol. 84:508–512. 1962.—The characteristics and requirements for growth of bacterial (Streptococcus faecalis) and yeast (Saccharomyces cerevisiae) protoplasts were established and the effect of a variety of antibacterial and antifungal antibiotics determined. A clear differentiation was obtained between such inhibitors of bacterial cell wall synthesis as penicillin and cycloserine, which did not prevent protoplast growth, and all others, antibacterial and antifungal, which inhibited protoplasts and intact organisms at the same range of concentration. Novobiocin, previously reported to inhibit bacterial wall synthesis, was also effective against a reaction(s) essential to the growth of S. faecalis protoplasts. The antibacterial action of streptomycin, neomycin, and kanamycin was essentially eliminated by the high salt concentration needed to maintain the protoplasts. Removal of the cell wall did not significantly increase antibiotic susceptibility of a resistant species. Protoplasts of Bacillus megaterium were insensitive to the antifungal agent, nystatin, and did not bind it to any detectable degree. Thus, the yeast or bacterial cell wall does not appear to play a major role in determining relative antibiotic susceptibility by masking internal sensitive target sites. A variety of antifungal antibiotics tested on the growth of log-phase yeast cells failed to produce osmotically fragile forms.